2015
DOI: 10.1124/mol.114.097402
|View full text |Cite
|
Sign up to set email alerts
|

Activating and Inhibitory Functions of WNT/β-Catenin in the Induction of Cytochromes P450 by Nuclear Receptors in HepaRG Cells

Abstract: The WNT/b-catenin signaling pathway has been identified as an important endogenous regulator of hepatic cytochrome P450 (P450) expression in mouse liver. In particular, it is involved in the regulation of P450 expression in response to exposure to xenobiotic agonists of the nuclear receptors constitutive androstane receptor (CAR), aryl hydrocarbon receptor (AhR), and Nrf2. To systematically elucidate the effect of the WNT/b-catenin pathway on the regulation and inducibility of major human P450 enzymes, HepaRG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 48 publications
(68 reference statements)
2
29
0
1
Order By: Relevance
“…Regarding inducibility of CYP2C8, the PXR-receptor seems to be the most important nuclear receptor, because typical PXR ligands/activators strongly induce CYP2C8 in vitro (Ferguson et al, 2005;) and can cause induction of CYP2C8 also in vivo, whereas ligands of the other nuclear receptors cause only moderate induction of CYP2C8 in vitro (Ferguson et al, 2005; and have not been shown to markedly induce CYP enzymes in vivo in humans. PXR activators, such as phenobarbital, hyperforin (an ingredient of St. John's wort), and rifampin, have increased CYP2C8 expression at mRNA, protein, and activity levels several-fold in vitro Gerbal-Chaloin et al, 2001;Rae et al, 2001;Nishimura et al, 2002;Raucy et al, 2002;Madan et al, 2003;Ferguson et al, 2005;Komoroski et al, 2005;Thomas et al, 2015). In addition, certain other compounds, including ritonavir, nelfinavir, cyclophosphamide, lithocholic acid, and paclitaxel can induce CYP2C8 presumably by a PXR-mediated mechanism in vitro (Chang et al, 1997;Dussault et al, 2001;Synold et al, 2001;Ferguson et al, 2005;Dixit et al, 2007).…”
Section: Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding inducibility of CYP2C8, the PXR-receptor seems to be the most important nuclear receptor, because typical PXR ligands/activators strongly induce CYP2C8 in vitro (Ferguson et al, 2005;) and can cause induction of CYP2C8 also in vivo, whereas ligands of the other nuclear receptors cause only moderate induction of CYP2C8 in vitro (Ferguson et al, 2005; and have not been shown to markedly induce CYP enzymes in vivo in humans. PXR activators, such as phenobarbital, hyperforin (an ingredient of St. John's wort), and rifampin, have increased CYP2C8 expression at mRNA, protein, and activity levels several-fold in vitro Gerbal-Chaloin et al, 2001;Rae et al, 2001;Nishimura et al, 2002;Raucy et al, 2002;Madan et al, 2003;Ferguson et al, 2005;Komoroski et al, 2005;Thomas et al, 2015). In addition, certain other compounds, including ritonavir, nelfinavir, cyclophosphamide, lithocholic acid, and paclitaxel can induce CYP2C8 presumably by a PXR-mediated mechanism in vitro (Chang et al, 1997;Dussault et al, 2001;Synold et al, 2001;Ferguson et al, 2005;Dixit et al, 2007).…”
Section: Inductionmentioning
confidence: 99%
“…Here, to be brief, we usually report only fold-changes of the mean AUC values caused by interactions. Of note, e.g., interindividual genetic 212 Antihyperlipidemic,PPARa agonist 4-fold in HepaRG cells Thomas et al, 2015 variation in the activity of drug metabolizing enzymes and transporters can cause a considerable variability in the extent of drug interactions. In particular, it is important to note that in an individual patient the exposure to a victim drug can change much more than the generally reported mean change.…”
Section: A General Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recently intricate interactions between Wnt/β-catenin signaling, lipid homeostasis, and drug biotransformation capacity that may be of clinical relevance under diseased conditions such as obesity, hepatic steatosis, and cancer have been suggested [24]. In the current study, expression of the reporter β-galactosidase could also be located in pericentral hepatocytes under sham conditions.…”
Section: Discussionmentioning
confidence: 60%
“…Members of the nuclear receptor superfamily function as ligand-activated transcription factors and play critical roles in nearly every aspect of development and adult physiology [73]. Interestingly, it has been reported that the Wnt/β-catenin signaling pathway is crucial for PXR activity and notably that β-catenin is required for PXRmediated induction of target gene expression [74].…”
Section: Pxrmentioning
confidence: 99%